Calculation of the Bi-Ga-Al-As phase diagram - Antochshenko, V.S.; Francev, Yu.V.; Lavrichshev, O.A.; Antochshenko, E.V. (Recent Contributions to Physics, 2012)
The Bi-Ga-Al-As quaternary phase diagram is calculated on the basis of quasi regular solution method in temperature range of 600-900oC. Using the relevant binary phase diagrams, liquid phase interaction parameters W Bi–Al, W Bi-As и W Bi–Ga is calculated. The temperature dependence of solubility of GaAs into Bi-Ga solvents is obtained. Fields of AlGaAs solid solutions crystallization are defined. Effect of Ga and Al on the GaAs dissolution is investigated.